Takeaway food, sugar-sweetened beverages and preclinical cardiometabolic phenotypes in children and adults. (25th November 2020) - Saraf, Shweta; Grobler, Anneke; Liu, Richard S; Liu, Mengjiao; Wake, Melissa; Olds, Tim; Lycett, Kate; Juonala, Markus; Ranganathan, Sarath; Burgner, David; Kerr, Jessica A
Abstract: Aims: To investigate relationships between takeaway food and sugar-sweetened beverage (SSB) consumption with cardiometabolic phenotypes during childhood and mid-adulthood. Method: Design: Cross-sectional Child Health CheckPoint within the national population-representative Longitudinal Study of Australian Children. Participants: 1838 children (mean age 11.5 years; 49.1% female) and 1846 adults (mean age 43.7 years; 87.6% female). Exposures: Self-reported takeaway food and SSB consumption ('frequent': ≥ weekly). Outcomes: Functional (pulse wave velocity (PWV), blood pressure (BP)) and structural (carotid intima-media thickness, retinal microvascular calibre) preclinical cardiovascular phenotypes; lipids (total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides). Analysis: Linear regression (exposure: takeaway or SSB consumption, individually or together) adjusted for age, sex and socio-economic position; and mediation analysis for body mass index (BMI). Results: Associations were small among children (standardized mean difference (SMD) ≤0.15). In adults, associations were stronger with functional, but not structural, cardiovascular phenotypes and lipids, particularly for frequent takeaway food consumption (e.g. PWV (0.20 m/s; 95% confidence interval (CI) 0.03 to 0.37); systolic (3.3 mmHg; 95% CI 1.3 to 5.3) and diastolic BP (1.4 mmHg; 95% CI 0.2 to 2.6); LDL (0.10 mmol/L; 95% CI 0.02 to 0.18); HDL (−0.14 mmol/L; 95% CI −0.19 to −0.10) and triglycerides (0.30 mmol/L; 95% CI 0.12 to 0.48)]. BMI mediated associations between takeaway food consumption and PWV, BP, HDL and TG (proportion of mediation 34% to 75%), while mediation effects were smaller for SSB consumption. Conclusions: Frequent takeaway food consumption in adults was associated with adverse blood lipids and vascular function (mainly via BMI). Lack of strong associations in children highlights opportunities for prevention.